A ecologia é “in loco” e não internacional: a participação das empresas de papel-celulose na promoção de um desenvolvimento sustentável em Três Lagoas (MS) - Oliveira, Caroline Barbosa Souza de (2020)
The need to discuss a solution to the urgent environmental and social problems related to the expansion of capital in recent years, has intensified as the risks have become real for the condition of human life in the future. The creation of a global “sustainable development”, which accommodates more conscious commercial practices, has been worked on since the last century, mainly in the orbit of international politics. However, this development model is comprehensive and has consistent barriers to be scientifically measured - measuring Sustainable Development is undoubtedly a difficult and exploratory task. Thus, this dissertation research will bring an analysis of the performance of the cellulose paper companies in Três Lagoas (MS), in the period 2008-2018. It is verified whether they comply with measures that, in fact, encourage green and more inclusive development in the region. For this, we used primary and secondary data obtained through official reports, in publicly accessible channels, and focused on quantitative and qualitative research to answer the following question: Do Fibria and Eldorado Brasil Celulose promote sustainable development in Três Lagoas? . We understand that the well-being of a population is a combination of many factors, but these industries have great influences on the economy, politics and the environment in this municipality in Mato Grosso do Sul. That said, the research carried out allows the following conclusions: a) there are serious failures in the inspection of public environmental agencies to verify whether environmental laws are being obeyed by these companies in the region; b) there are indications that there may be contamination of the Paraná River and congestion of the local road system, due to the activities of these industries; c) there are few official reports that favor checking, in fact, the environmental impact caused by Fibra and Eldorado Brasil Celulose in Três Lagoas; d) the social programs and projects of these companies for the socio-environmental development of the municipality are not very specific. Finally, there is no strategic plan for sustainable development in Três Lagoas, much less a future plan instance these companies shut down their activities in the municipality.